Pancreatic neuroendocrine neoplasms : practical approach to diagnosis, classification, and therapy - La Rosa, Stefano; Sessa, Fausto (Springer, 2015)
This book provides a broad overview of pancreatic neuroendocrine neoplasms, focusing on the most important developments in the technologies used to diagnose, classify, and treat them. After a historical and epidemiological overview, the opening chapters examine the various diagnostic approaches (radiology, nuclear medicine, endocrinology, cytology, and immunohistochemistry) and discuss the WHO classification. The functioning and nonfunctioning tumor types are then fully discussed, covering epidemiology, diagnosis, morphology, and prognosis of each entity. Careful consideration is given to the molecular features that have contributed in understanding the pathogenesis of such neoplasms and may have potential implications for the diagnostic and therapeutic pathways. The final chapters consider the surgical and medical approaches to therapy, providing a practical and analytical overview of the available options. The book is written by a multidisciplinary team of worldwide-recognized experts and is addressed to radiologists, nuclear medicine physicians, endocrinologists, pathologists, surgeons, and oncologists.